Marital satisfaction among spouses in inter-and intra -ethnic marriages in the Kumasi Metropolis, Ghana - Bentil, Josephine Anterkyi (University of Cape Coast, 2021)
This study examined marital satisfaction among inter-and-intra-ethnic marriages in the Kumasi Metropolis, Ghana. It adopted a cross sectional approach and an embedded research design method. Five hundred and fifty seven spouses were selected using a multi-stage sampling method comprising; cluster, purposive, stratified, and simple random sampling (Lottery) methods respectively to sample the spouses from the accessible population. Questionnaire and interviews were employed to collect data. Data were statistically analysed through the use of frequencies, means, standard deviation, independent sample t-test, Structural Equation Modelling Multi-group, and the one-way multivariate analysis of variance (MANOVA). Thematic analysis was also used for the qualitative aspect of the study. A major finding of the study was that spouses in inter and intra-ethnic marriages were not satisfied with the inheritance pattern for their children. Therefore, it is, recommended that spouses in both inter-and intra- ethnic marriages should be educated to write out a will while alive with the help of counsellors, legal practitioners in order that their children receive what is appropriately due them. Further, assets acquired during the marriage should be registered in the names of their children to avoid confusion and conflicts after their demise when in accordance with PNDC Law 111 (Interstate succession Law) of Ghana. The result of the study further indicated that, spouses who were 20-30 years significantly enjoy marital satisfaction better than those aged 41-50 years. It is therefore, recommended that marriage counsellors in the various religious organisations continuously organise programmes such as talks and seminars to the young spouses and most especially the mature spouses to spice up their marital satisfaction.
xiii, 267p :,ill